Modelagem com etnomatemática: uma situação a-didática para o ensino - DIAS, Markus Benedito Santos (Universidade Federal do Pará, 2017)
Mathematics education is concerned with solving the various problems relating to the teaching and learning of mathematics. Among these problems, there is in particular the difficulty of the students and teachers can not articulate the school mathematical knowledge to various situations imposed by reality, especially those belonging to their cultural world. The aim of this paper was to study scientific everyday practices of a cultural group, and from the assumptions of mathematical modeling approach with the Ethnomatematics, show that both can be characterized as a situation a-didactic according to the perspective of the Theory of Didactic Situations (TSD). By not directly involved students in this research, we a priori study some works that indicate interlacing Modeling to Ethnomatematics and also create an activity involving the knowledge of master craftsmen, responsible for the construction of vessels, using our tacit knowledge to be analyzed. The intention was to check the paths taken through the process of modeling and comparing them to the phases present in the TSD. The results obtained allowed us to understand that the themes of cultural imprint can be used as a motivating environment in the learning process to be part of the reality of the students of this region, also indicated the use of modeling with the input of Ethnomatematics can be characterized as a situation a-didactic not attempt to modify the set of mathematical knowledge of the other, here including their arguments and cultural references, to enforce what the student should learn.